LA NOUVELLE DE UN POETA: LA FANFARLO DE CHARLES BAUDELAIRE - Camero Pérez, Carmen (Anales de Filología Francesa, 2006)
A poet’s short story: La Fanfarlo by Charles Baudelaire. First published in 1847, when he was only twenty-five years old, La Fanfarlo is the short story of a young man, although not that one of a beginner. A careful reading allows to elicit a poetic theory for the short story, where you can notice briefness, realism, oral expression and exceptional characters within the framework of a story build up with irony and intertextual cross-reference, not without some autobiographical amount.